2000
DOI: 10.1002/1529-0131(200009)43:9<1951::aid-anr5>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Synovial macrophage depletion with clodronate‐containing liposomes in rheumatoid arthritis

Abstract: A single IA administration of clodronate liposomes leads to macrophage depletion and decreased expression of adhesion molecules in the synovial lining in patients with longstanding RA. The procedure is well tolerated, and its therapeutic potential is currently under investigation. The expression of adhesion molecules in the sublining layers reflects ongoing inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
97
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 197 publications
(106 citation statements)
references
References 48 publications
5
97
0
Order By: Relevance
“…Stimulation of Fc␥RII/Fc␥RIII expressed by synovial intima cells may regulate proinflammatory cytokine production in the subintima. This is consistent with earlier studies in which it was shown that selective removal of intima cells from the RA joint by clodronate liposome treatment down-regulates TNF␣ in the subintima (57).…”
Section: Discussionsupporting
confidence: 93%
“…Stimulation of Fc␥RII/Fc␥RIII expressed by synovial intima cells may regulate proinflammatory cytokine production in the subintima. This is consistent with earlier studies in which it was shown that selective removal of intima cells from the RA joint by clodronate liposome treatment down-regulates TNF␣ in the subintima (57).…”
Section: Discussionsupporting
confidence: 93%
“…Increased numbers of macrophages, which can be activated to produce mediators of inflammation, are a prominent feature of inflammatory lesions, in particular those of a chronic nature (4), and their depletion from inflamed tissue (5) and from the circulation (6) can have profound benefit. With regard to RA, it has been observed that the number of macrophages in the synovial tissue correlates with the degree of joint erosion (7,8), and that increased numbers of macrophages are an early hallmark of active disease (9,10).…”
Section: Synovial Macrophage Number As An Ra Biomarkermentioning
confidence: 99%
“…administration of liposomeencapsulated dichloromethylene-bisphosphonate (clodronate liposomes). Clodronate liposomes have been used to study the role of macrophages in a number of chronic diseases (60,61). Clodronate is a cytotoxic compound that induces apoptotic cell death of macrophages when it is delivered encapsulated in a phospholipid bilayer liposome.…”
mentioning
confidence: 99%